PERAN GURU PAI DALAM PENGUATAN NILAI SPIRITUAL DAN MORAL DI ERA SOCIETY 5.0 - Anita Mulia Arifiani; Khoiru Nisa; Muammar Muammar; Anggita Novitasari; Nur Azizah; Desti Widiani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The digital transformation accompanying the development of Society 5.0 has created new challenges for education, particularly in maintaining a balance between technological advancement and students’ character development. In the context of Islamic Religious Education (IRE), teachers are no longer limited to the role of transmitting religious knowledge but also play a crucial role in shaping the spiritual and moral development of a generation growing up in an increasingly digitalized environment. This study examines how IRE teachers fulfill these responsibilities through a review of relevant scholarly literature. The research employed a library research approach, utilizing scientific articles, books, and other academic sources as the primary data. Data were collected through documentation techniques and analyzed using content analysis involving the processes of selection, categorization, and synthesis of findings. The results indicate that IRE teachers perform interconnected roles as spiritual mentors, learning facilitators, innovators in technology integration, character role models, and promoters of digital literacy grounded in Islamic values. The strengthening of students’ spiritual and moral dimensions is achieved through the integration of digital technology with Islamic teachings, the habituation of religious practices, the implementation of contextual learning, and the development of twenty-first-century competencies. These findings demonstrate that IRE teachers occupy a strategic position in fostering students who can adapt to technological advancements without losing their value orientation, enabling them to grow as religious, ethical, and resilient individuals capable of navigating the dynamics of modern society. ABSTRAK Transformasi digital yang mengiringi perkembangan Society 5.0 menghadirkan tantangan baru bagi dunia pendidikan, khususnya dalam menjaga keseimbangan antara kemajuan teknologi dan pembentukan karakter peserta didik. Dalam konteks Pendidikan Agama Islam (PAI), keberadaan guru tidak lagi terbatas pada fungsi transfer pengetahuan keagamaan, melainkan turut menentukan arah perkembangan spiritual dan moral generasi yang hidup di tengah arus digitalisasi. Kajian ini menelaah bagaimana Guru PAI menjalankan peran tersebut melalui penelusuran berbagai sumber ilmiah yang relevan. Penelitian dilaksanakan dengan pendekatan studi kepustakaan yang memanfaatkan artikel ilmiah, buku, dan berbagai literatur akademik sebagai sumber data utama. Informasi yang diperoleh dihimpun melalui dokumentasi, kemudian diolah menggunakan analisis isi melalui proses pemilahan, pengelompokan, dan sintesis temuan. Hasil kajian memperlihatkan bahwa Guru PAI menjalankan fungsi yang saling terhubung, mencakup pembimbing spiritual, fasilitator proses belajar, inovator dalam pemanfaatan teknologi, teladan dalam pembentukan karakter, serta penggerak literasi digital yang berlandaskan nilai-nilai Islam. Penguatan aspek spiritual dan moral peserta didik dilakukan melalui pemaduan teknologi digital dengan ajaran keislaman, pembiasaan aktivitas religius, penerapan pembelajaran yang dekat dengan realitas kehidupan, serta pengembangan kompetensi abad ke-21. Temuan ini menunjukkan bahwa Guru PAI memegang posisi penting dalam membentuk peserta didik yang mampu beradaptasi dengan perkembangan teknologi tanpa kehilangan orientasi nilai, sehingga tumbuh sebagai individu yang religius, berkarakter, dan siap menghadapi dinamika masyarakat modern.